2022
DOI: 10.3390/bioengineering9120744
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering Applied to Skeletal Muscle: Strategies and Perspectives

Abstract: Muscle tissue is formed by elongated and contractile cells with specific morphofunctional characteristics. Thus, it is divided into three basic types: smooth muscle tissue, cardiac striated muscle tissue and skeletal striated muscle tissue. The striated skeletal muscle tissue presents high plasticity, regeneration and growth capacity due to the presence of satellite cells, quiescent myoblasts that are activated in case of injury to the tissue and originate new muscle fibers when they differentiate. In more sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Infected and detached myotubes might be rinsed off with media change. This problem may be addressed by improving host cell attachment to the culture vessel using various methods ( Madden et al, 2015 ; Bettadapur et al, 2016 ; Denes et al, 2019 ; Martins et al, 2022 ). Finally, cellular senescence may also pose a limit on the maximal passages of KD3 cells and may be ameliorated by reversine treatment ( Rajabian et al, 2023 ).…”
Section: General Notes and Troubleshootingmentioning
confidence: 99%
“…Infected and detached myotubes might be rinsed off with media change. This problem may be addressed by improving host cell attachment to the culture vessel using various methods ( Madden et al, 2015 ; Bettadapur et al, 2016 ; Denes et al, 2019 ; Martins et al, 2022 ). Finally, cellular senescence may also pose a limit on the maximal passages of KD3 cells and may be ameliorated by reversine treatment ( Rajabian et al, 2023 ).…”
Section: General Notes and Troubleshootingmentioning
confidence: 99%
“…Muscle tissue engineering requires the differentiation of skeletal muscle myoblasts or muscle precursors into multinucleated myotubes [ 130 ]. For muscle injury, tissue engineering is used primarily to repair the damage by mimicking the microenvironmental cues of existing muscle tissue [ 131 ]. Sicari et al demonstrated that acellular biologic scaffolds composed of ECM can significantly promote muscle regeneration in preclinical rodent models and human patients with volumetric muscle loss [ 132 ].…”
Section: Bioactive Materials For Musculoskeletal Diseasesmentioning
confidence: 99%
“…Therefore, novel therapeutic strategies for the efficient treatment of muscle loss are urgently needed. The emerging technology of muscular tissue engineering using well-designed biomaterials holds promise in rehabilitating defective muscle [3].…”
Section: Introductionmentioning
confidence: 99%